PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE, DAN CAPITAL TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Mala Sharfina Adavi; Agus Purwanto (Diponegoro Journal of Accounting, 2025)
This study was conducted to analyze the influence of Risk Profile, Good Corporate Governance (GCG), and Capital on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021 to 2024. In this research, the Risk Profile is measured using two main indicators: Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR). GCG is assessed using the self-assessment method, which is an internal evaluation of the implementation of good corporate governance principles. Meanwhile, Capital is measured using the Capital Adequacy Ratio (CAR).The dependent variable in this study is financial performance, measured by two profitability ratios: Return on Assets (ROA) and Return on Equity (ROE). This research uses secondary data obtained from the annual financial statements of the sampled banking companies, selected using purposive sampling technique.The results show that NPL has a negative and significant effect on both ROA and ROE, indicating that a higher level of non-performing loans leads to a decline in financial performance. LDR has a positive but not significant effect, meaning that although higher credit distribution may potentially increase income, it does not directly improve profitability. GCG has a positive and significant effect, showing that consistent implementation of good corporate governance practices contributes to improved efficiency and financial performance. Meanwhile, CAR has a negative and significant effect, suggesting that excessive capital allocation may not always be effective in supporting profitability growth in banking institutions